Diatomaceous earth filtration for safe drinking water - Fulton, George P. (ASCE Press, 2000)
Provides engineering professionals with information needed for evaluating diatomaceous earth (DE) filtration as an alternative method of water treatment. Gives background performance data and tips for application to conventional and unusual treatment situations, and walks through the entire design procedure, from different types of DE filters and equipment options to pilot testing and final design of treatment facilities. Coverage includes wear and safety, site development, start-up and operation, and routine maintenance. Fulton has served for many years as the technology leader of water treatment for a major environmental consulting engineering firm.